2006
DOI: 10.1353/mcb.2006.0080
|View full text |Cite
|
Sign up to set email alerts
|

On the Failure of Purchasing Power Parity for Bilateral Exchange Rates after 1973

Abstract: Point estimates suggest mean reversion in real exchange rates; however, it still remains uncomfortable that models without any mean reversion are often compatible with data from the floating period. Studies with data over longer periods find mean reversion, but at the cost of mixing in data from earlier exchange rate arrangements. Pooling the floating period data potentially mixes country pairs with and without mean reversion. We examine tests for mean reversion for individual country pairs where greater power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 36 publications
2
39
0
Order By: Relevance
“…These findings are largely consistent with the Bayesian results of Schotman and Dijk (1991), who find that the real variables are trend-stationary while nominal ones are difference-stationary. For the real exchange rates studied by Elliott and Pesavento (2006), both the ADF and DF-GLS tests demonstrate strong support for purchasing power parity at the decision-based levels, in contrast with the results at a conventional level. In addition, most of the real interest rates studied by Rapach and Weber (2004) are found not to have a unit root, based on the ADF and DF-GLS tests at the decision-based levels of significance.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…These findings are largely consistent with the Bayesian results of Schotman and Dijk (1991), who find that the real variables are trend-stationary while nominal ones are difference-stationary. For the real exchange rates studied by Elliott and Pesavento (2006), both the ADF and DF-GLS tests demonstrate strong support for purchasing power parity at the decision-based levels, in contrast with the results at a conventional level. In addition, most of the real interest rates studied by Rapach and Weber (2004) are found not to have a unit root, based on the ADF and DF-GLS tests at the decision-based levels of significance.…”
Section: Discussionmentioning
confidence: 75%
“…In this section, using the decision-based significance level and the calibration rules, we examine the extended Nelson-Plosser data set for U.S. macroeconomic time series; the real exchange rates covered by Elliott and Pesavento (2006); the real interest rates studied by Rapach and Weber (2004); and the nominal interest rates used by Neely and Rapach (2008). Table 5 reports the results for the extended Nelson-Plosser data.…”
Section: Re-evaluation Of Past Empirical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the ADF and DF-GLS tests are conducted at the optimal levels, many time series in the Nelson-Plosser data set are found be trendstationary including the real income and money stock. For the real exchange rates examined by Elliott and Pesavento (2006), the ADF and DF-GLS tests conducted at the optimal level favor the stationarity for nearly all rates, generating strong support for the purchasing power parity. Furthermore, most of the real interest rates series covered in Rapach and Weber's (2004) study are found to be stationary at the optimal levels.…”
Section: Introductionmentioning
confidence: 91%
“…As a consequence, not considering the multivariate dimension of the problem leads to a loss in the power of the test. Using covariates also allows to some extent to couple unit root testing and economic theory, because economic theory can be used as a guideline to chose the appropriate covariates to be included in the analysis (see e.g., Amara and Papell 2006;Elliott and Pesavento 2006), although other approaches can be used as well (Lee and Tsong 2009). …”
Section: Introduction and Statistical Backgroundmentioning
confidence: 99%